Migrant workers, self‐reliance, and the propensity to hold income protection insurance by country of residence. (26th February 2018) - Clark, Gordon L.; McGill, Sarah; Cuñado, Juncal
Abstract: Utilising a large comparative survey across 11 countries, it is shown that country effects condition the individual uptake of income protection insurance and that shared attributes, including labour market status, are important factors in determining the take‐up of income protection insurance, whatever the respondents' country of residence. We observed differences in the respondents' coping strategies, including self‐reliance, and were able to distinguish between migrant workers and those who work in their country of origin, along with the "special" case of the Australian respondents. These findings have implications for the ongoing debate on the labour market effects of globalisation and the significance of national institutions and regulatory practices.